2010
DOI: 10.1167/iovs.09-4498
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Cultured Human Keratocytes and Myofibroblasts to Ethyl Pyruvate: A Microarray Analysis of Gene Expression

Abstract: These EP-induced phenotypic changes in myofibroblasts indicate the potential of EP as a therapeutic agent in corneal wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Taken together, the anti-inflammatory effects of EP in cornea documented in the present study, as well as its antifibrotic and antiproliferative properties reported previously, 39 indicate that EP can be a potential chemotherapeutic agent for attenuating corneal inflammation and modulating corneal wound healing.…”
Section: Figuresupporting
confidence: 87%
See 1 more Smart Citation
“…Taken together, the anti-inflammatory effects of EP in cornea documented in the present study, as well as its antifibrotic and antiproliferative properties reported previously, 39 indicate that EP can be a potential chemotherapeutic agent for attenuating corneal inflammation and modulating corneal wound healing.…”
Section: Figuresupporting
confidence: 87%
“…19 In our previous study, we observed that EP inhibited corneal myofibroblast proliferation, and microarray analysis indicated that EP inhibits the cell cycle/cell death/cancer genes, increases the NRF2-mediated antioxidant response, and modifies the subset of profibrotic genes. 39 It has been documented that proinflammatory DNAbinding protein, HMGB1 secretion, is inhibited by EP in vitro and in vivo. 10 In conclusion, EP exhibited anti-inflammatory effects very similar to those of the steroidal drug PRED FORTE.…”
Section: Figurementioning
confidence: 99%
“…Endogenous SO 2 was produced from L-cysteine in a two-step reaction, in which the later step was catalyzed by AAT and resulted in equimolar pyruvate as well 7 8 32 . Previous studies showed that pyruvate could modulate TGF-β signaling 33 34 . However, whether the effects of AAT manipulation on collagen remodeling were caused by SO 2 or pyruvate had not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between increased pyruvate‐r and less tiredness, reduced stiffness and less limitations in strength in the injured limb suggests that pyruvate is involved in healing pathways leading to improved mechanical properties, for example, by conversion of collagen type III (scar tissue) into collagen type I (mature tissue). Pyruvate is known among other things to promote wound healing by augmenting the antioxidant response of the tissue and acting antifibrotically, which minimizes the fibrotic collagen type III . The finding of less experience of pain related to higher pyruvate‐r may reflect the fact that pyruvate reduces fibrosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvate is known among other things to promote wound healing by augmenting the antioxidant response of the tissue and acting antifibrotically, which minimizes the fibrotic collagen type III. 9,21,22 The finding of less experience of pain related to higher pyruvate-r may reflect the fact that pyruvate reduces fibrosis and inflammation. Interestingly, addition of pyruvate after injury has recently been demonstrated to exhibit strong anti-inflammatory and anti-oxidative effects in tissue repair.…”
Section: Discussionmentioning
confidence: 99%